Damping wings in the Lyman-α forest: a model-independent measurement of the neutral fraction at 5.4 < z < 6.1 - Spina, Benedetta; Bosman, Sarah; Davies, Frederick B.; Gaikwad, Prakash; Zhu, Yongda (Astronomy and astrophysics, 2024)
Context. Recent observations have positioned the end point of the Epoch of Reionization (EoR) at a redshift of z ∼ 5.3. However, observations of the Lyman-α forest have not yet been able to discern whether reionization occurred slowly and late, with substantial neutral hydrogen persisting at a redshift of ∼6, or rapidly and earlier, with the apparent late end driven by the fluctuating ultraviolet background. Gunn-Peterson (GP) absorption troughs are solid indicators that reionization is not complete until z = 5.3, but whether they contain significantly neutral gas has not yet been proven. Aims. We aim to answer this question by directly measuring, for the first time, the neutral hydrogen fraction (xHI) at the end of the EoR (5 ≲ z ≲ 6) in high-redshift quasar spectra. Methods. For high neutral fractions, xHI ≳ 0.1, GP troughs exhibit damping wing (DW) absorption extending over 1000 km s−1 beyond the troughs. While conclusively detected in Lyman-α emission lines of quasars at z ≥ 7, DWs are challenging to observe in the general Lyman-α forest due to absorption complexities and small-scale stochastic transmission features. Results. We report the first successful identification of the stochastic DW signal adjacent to GP troughs at redshifts of z = 5.6 through careful stacking of the dark gaps in the Lyman-α forest (S/N = 6.3). We use the signal to present a measurement of the corresponding global xHI = 0.19 ± 0.07 at 1σ (2σ) at z = 5.6 and a limit of xHI < 0.44 at z = 5.9. Conclusions. The detection of this signal demonstrates the existence of substantially neutral islands near the conclusion of the EoR, unequivocally signaling a late-and-slow reionization scenario.